2022
DOI: 10.3389/fonc.2022.873293
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Restricted Diet Regulates the Tumor Immune Microenvironment and Prevents Tumor Growth in Lung Adenocarcinoma

Abstract: BackgroundLung cancer is the second common cancer type in western countries and has a high mortality. During the development and progression of the tumor, the nutrients in its environment play a central role. The tumor cells depend crucially on glucose metabolism and uptake. Tumor cell metabolism is dominated by the Warburg effect, where tumor cells produce large amounts of lactate from pyruvate under aerobic conditions. We thus reasoned that, reducing carbohydrates in the diet might support anti-tumoral effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Under glucose-deprived conditions, a decrease in cell count was evident after 48 hours in 5mM SB, as well as in comparison with 1 to 5mM SB ( Figure 1C ). The results in Figure 1C also show distinct growth restriction caused by glucose deprivation, which we described previously ( 14 ), resulting in a reduced cell count after 48 and 72h in the absence of SB stimulation. The addition of 5mM SB resulted in a further reduced average percentage of cell count in the absence of glucose.…”
Section: Resultssupporting
confidence: 86%
“…Under glucose-deprived conditions, a decrease in cell count was evident after 48 hours in 5mM SB, as well as in comparison with 1 to 5mM SB ( Figure 1C ). The results in Figure 1C also show distinct growth restriction caused by glucose deprivation, which we described previously ( 14 ), resulting in a reduced cell count after 48 and 72h in the absence of SB stimulation. The addition of 5mM SB resulted in a further reduced average percentage of cell count in the absence of glucose.…”
Section: Resultssupporting
confidence: 86%
“…One problem is nutrition which can be imbalanced and thus might support the tumor growth 37,38 . We recently reported our investigation on the role of blood glucose in our cohort of patients with LUAD 4 . Other studies also demonstrated that glucose restriction in the diet resulted in decreased tumor development in a murine model of lung cancer 4,39 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported our investigation on the role of blood glucose in our cohort of patients with LUAD 4 . Other studies also demonstrated that glucose restriction in the diet resulted in decreased tumor development in a murine model of lung cancer 4,39 . Following up this observation, we asked about the role of lipids in the same cohort of patients with LUAD 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, blockade of lactate production via inhibition of pyruvate dehydrogenase with oxamate led to increased CD8+ T cell infiltration, reduced NSCLC tumor growth and improved responses to anti-PD-1 antibodies [99]. In line with this, a recent report showed how a glucose-restricted diet led to reduced tumor growth and increased intratumoral infiltration of CD8 effector memory T cells and NK cells [100].…”
Section: Lactatementioning
confidence: 78%